A particle moves on a straight line with velocity function v(t)= sin((alpha)(t))cos((alpha)(t))^2 . Find its position function s(t) if s(0) = 2.

2 Answers | Add Yours

sciencesolve's profile pic

sciencesolve | Teacher | (Level 3) Educator Emeritus

Posted on

You need to integrate the given velocity function to find the position of particle such that:

`s(t) = int (sin alpha*t*cos alpha*t)^2 dt`

You need to use the half angle identities such that:

`sin^2 alpha*t = (1 - cos 2alpha*t)/2`

`cos^2 alpha*t = (1+ cos 2alpha*t)/2`

`s(t) = int (1 - cos 2alpha*t)/2*(1 + cos 2alpha*t)/2 dt`

`s(t) = (1/4)int (1 - cos 2alpha*t)(1 +cos 2alpha*t) dt`

You need to convert the integrand into a difference of squares such that:

`s(t) = (1/4)int (1 - cos^2 (2alpha*t)) dt`

Using the property of linearity such that:

`s(t) = (1/4)int dt- (1/4)int (cos^2 (2alpha*t)) dt`

`cos^2 (2alpha*t) = (1 + cos 4alpha*t)/2`

`s(t) = (1/4)int dt- (1/4)int(1 + cos 4alpha*t)/2 dt`

`s(t) = (1/4)int dt - (1/8)int (1 + cos 4alpha*t) dt`

`s(t) = (1/4)int dt - (1/8)int dt - (1/8)int (cos (4alpha*t)) dt`

`s(t) = (1/8)int dt - (1/8)int (cos (4alpha*t)) dt`

`s(t) = (1/8)(t - (sin (4alpha*t))/4) + c`

The problem provides the information that `s(0) = 2` , hence, you may evaluate the constant `c`  such that:

`s(0) = (1/8)(0 - (sin (0))/4) + c`

Since si`n 0 = 0 ` yields:

`s(0) = c => c = 2`

Hence, evaluating the position of the particle, under the given conditions, yields `s(t) = (1/8)(t - (sin (4alpha*t))/4) + 2` .

jeew-m's profile pic

jeew-m | College Teacher | (Level 1) Educator Emeritus

Posted on

V(t)

`= sinalphat*(cosalphat)^2`

 

Position function is given by the integration of vector function.

S(t)

`= int V(t)dt`

`= intsinalphat*(cosalphat)^2*dt`

 

Let

`x = cosalphat`

`(dx)/dt = -sinalphat*alpha`

`dx = -alpha*sinalphat*dt`

 

S(t)

`= intsinalphat*(cosalphat)^2*dt`

`= int -alpha*x^2dx`

`= -alpha int x^2dx`

`= -alpha(x^3/3)+C`

`= -alpha((cosalphat)^3/3)+C`

 

It is given that S(0) = 2

 

`2 = -alpha((cosalpha*0)^3/3)+C`

`2 = -alpha/3+C`

`C = 2+alpha/3`

 

`S(t) = -alpha((cosalphat)^3/3)+2+alpha/3`

So the position function is;

`S(t) = (alpha/3)(1-(cosalphat)^3)+2`

 

Sources:

We’ve answered 318,946 questions. We can answer yours, too.

Ask a question